Functional dynamic factor model for intraday price curves - Kokoszka, Piotr, author; Miao, Hong, author; Zhang, Xi, author; Journal of Financial Econometrics, publisher (Colorado State University. Libraries, 2015)
This article proposes a functional dynamic factor model for the evaluation of the impact of scalar– and curve–valued factors on the shapes of intraday price curves. The asymptotic theory leads to practically useful confidence intervals for the factor coefficients. The main findings pertain to the impact of the shapes of intraday oil futures on the shapes of intraday prices of blue chip stocks.
Published as: Journal of Financial Econometrics, vol. 13, no. 2, pp. 456-477, 2015, https://doi.org/10.1093/jjfinec/nbu004.
Keywords: functional factor model; intraday price curves; oil futures